«¿Precomprensión o preconcepción?»: Una replica a Javier Paricio - Casarotti, Luca (Tesserae iuris, 2023)
In a scholarly paper, Javier Paricio accuses a colleague, Luca Casarotti, of not really being the author of an article he signed, which according to Paricio he could not have written because of his blindness and young age. This article responds to the accusation, and brings the debate back to the merits of the historiographical issues.